Power estimation for four seater helicopter - Ibrahim, Ahmad Azlan Shah; Mohd. Jaafar, Mohammad Nazri (Faculty of Mechanical Engineering, 2008)
In helicopter design, generally there are three types of condition of interest, which are hover, vertical climb and forward flight. This paper describes the method for first estimation of power required for four-seater helicopter. The objective of this study is to estimate power for four-seater helicopter. Among the factors that affect the power required are the density effect of air at various altitudes, induced velocity along the blade, and horizontal force due to the fuselage, but only some of them will be studied in this paper. Methods used in this study to estimate the power is the momentum method. A parametric study on present helicopters in the market was performed to obtain initial specifications for the proposed helicopter. Based on these specifications, the weight estimation was determined according to Prouty method [1]. Using the momentum method and the specification for the helicopter, the power required was estimated. A computer program using MATLAB was also developed to expedite the power estimation calculations.